1986
DOI: 10.1152/ajpgi.1986.251.1.g70
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cholecystokinin and pancreatic growth during adaptation to dietary protein

Abstract: The relationship among plasma cholecystokinin (CCK), pancreatic growth, and food intake was studied in rats over a 2-wk period of adaptation from a very low-protein to a very high-protein diet. Rats adapted to a control diet (5% casein) were killed at 0900 (without fasting) at 0 h, 12 h, 24 h, 48 h, 7 days, or 14 days after transfer to a high-protein diet (75% casein). CCK was measured by bioassay using isolated pancreatic acini. Plasma CCK in high protein-fed rats was increased approximately threefold in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…165 It was also shown that dietary proteins that effectively stimulated CCK secretion were ineffective with the co-administration of exogenous trypsin 58 . 260 During the first few days of feeding a high-casein diet, plasma CCK levels were very high. 257 Substantial evidence indicated that CCK mediated the effects of trypsin inhibitor feeding and bile-pancreatic juice diversion on pancreatic growth.…”
Section: Role Of Cholecystokinin In Feedback Regulationmentioning
confidence: 99%
“…165 It was also shown that dietary proteins that effectively stimulated CCK secretion were ineffective with the co-administration of exogenous trypsin 58 . 260 During the first few days of feeding a high-casein diet, plasma CCK levels were very high. 257 Substantial evidence indicated that CCK mediated the effects of trypsin inhibitor feeding and bile-pancreatic juice diversion on pancreatic growth.…”
Section: Role Of Cholecystokinin In Feedback Regulationmentioning
confidence: 99%
“…Consumption of large amounts of protein induces growth of the adult rodent pancreas 5, 6. Dietary protein stimulates the release of gastrointestinal hormones and the growth promoting effects of dietary protein on the exocrine pancreas have been attributed to these hormones, particularly cholecystokinin (CCK) 7.…”
Section: Background and Aimsmentioning
confidence: 99%
“…When compared with healthy controls, in patients with anorexia nervosa, an earlier and greater rise in plasma CCK levels after a liquid meal was observed, a pattern which was normalised with nutrition therapy 18. Animal experiments have shown that—during adaptation to increased dietary proteins—there is a notable, although transient, increase in plasma CCK levels 19. On the contrary, after food deprivation, plasma CCK levels decrease rapidly and this decrease is followed by a reduction in duodenal CCK mRNA and mucosal CCK peptide levels.…”
mentioning
confidence: 98%